Ancient polyploidization events influence the evolution of the ginseng family (Araliaceae) - Gallego-Narbón, Angélica; Johnson, Gabriel; Fernández-Mazuecos, Mario; Wen, Jun; Valcárcel, Virginia (Frontiers in Plant Science, 2025)
IntroductionWhole genome duplication events (WGDs) have been recognized as major drivers of evolution in plants, especially when they involve hybridization (allopolyploidization). In this study we evaluated if WGDs acted as evolutionary forces at the origin and early divergence of the Asian Palmate group (AsPG) of the plant family Araliaceae. This clade encompasses most of the generic and species diversity as well as most of the polyploids of the family, and a role of hybridization in its origin has been suggested.MethodsIn order to test this hypothesis, we obtained nuclear and plastid time-calibrated phylogenomic trees including 80% of Araliaceae genera (37 genera, 237 species) using the Hyb-Seq approach. The role of WGDs in the early evolution of the AsPG was tested using ancestral chromosome number reconstructions based on chromosome counts for 62% of the sampled genera, while recent polyploidization events were explored by inferring ploidy of the sequenced species from allelic frequencies.ResultsPhylogenetic analyses of nuclear and plastid sequences provided highly resolved but incongruent topologies consistent with ancient hybridization not only for the origin of the AsPG, but also in the second most highly diverse clade of the family. Our ancestral chromosome number reconstructions supported that one or two WGDs preceded the origin of two of the three main clades of Araliaceae (AsPG and Polyscias-Pseudopanax), which could have acted as background variables necessary for the posterior diversification of these lineages. Ploidy inference based on allelic frequencies provided signal of recent polyploidization in the AsPG and the third main clade of Araliaceae (Aralia-Panax).ConclusionsIn summary, WGDs are linked to the origin of the main clades of the Araliaceae family, but the drivers of the strong diversification of the AsPG remain an open question.